Exploring new catechin derivatives as SARS-CoV-2 Mpro inhibitors from tea by molecular networking, surface plasma resonance, enzyme inhibition, induced fit docking, and metadynamics simulations. (December 2022) - Yang, Zi; Wang, Wei; Qi, Yan; Yang, Yi; Chen, Chen-Hui; Liu, Jia-Zheng; Chu, Gang-Xiu; Bao, Guan-Hu
Abstract: SARS-CoV-2 M pro (Mpro) is the critical cysteine protease in coronavirus viral replication. Tea polyphenols are effective M pro inhibitors. Therefore, we aim to isolate and synthesize more novel tea polyphenols from Zhenghedabai (ZHDB) white tea methanol-water (MW) extracts that might inhibit COVID-19. Through molecular networking, 33 compounds were identified and divided into 5 clusters. Further, natural products molecular network (MN) analysis showed that MN1 has new phenylpropanoid-substituted ester-catechin (PSEC), and MN5 has the important basic compound type hydroxycinnamoylcatechins (HCCs). Thus, a new PSEC (1, PSEC636) was isolated, which can be further detected in 14 green tea samples. A series of HCCs were synthesized (2 –6 ), including three new acetylated HCCs (3 –5 ). Then we used surface plasmon resonance (SPR) to analyze the equilibrium dissociation constants (KD ) for the interaction of 12 catechins and M pro . The KD values of PSEC636 (1 ), EGC-C (2 ), and EC-CDA (3 ) were 2.25, 2.81, and 2.44 μM, respectively. Moreover, compounds 1, 2, and 3 showed the potential M pro inhibition with IC50 5.95 ± 0.17, 9.09 ± 0.22, and 23.10 ± 0.69 μM, respectively. Further, we used induced fit docking (IFD), binding pose metadynamics (BPMD), and molecular dynamics (MD) to explore the stable binding pose of M pro -1, showing that 1 could tightly bond with the amino acid residues THR 26, HIS 41, CYS 44, TYR 54, GLU 166, and ASP 187 . The computer modeling studies reveal that the ester, acetyl, and pyrogallol groups could improve inhibitory activity. Our research suggests that these catechins are effective M pro inhibitors, and might be developed as therapeutics against COVID-19. Graphical abstract: Image 1 Highlights: Binding affinities of 12 catechins were tested by surface plasmon resonance technology. Catechins 1 –6 (1, 3 –5 are new) were identified as novel inhibitors of SARS-CoV-2 M pro . 1 -M pro complex were studied by induced-fit docking, binding pose metadynamics, and molecular dynamics. Benzene ring, hydroxyl, and acetyl groups of substituted p -coumaric acid interact with SARS-CoV-2 M pro . THR 26, HIS 41, CYS 44, TYR 54, GLU 166, and ASP 187 residues are the key binding sites.